Documentarista-historiador: a escritura fílmica da história no filme Céu aberto (1985), de João Batista de Andrade - Dias, Rodrigo Francisco (2014)
THE PRESENT WORK deals with the relations between Documentary Cinema and History of Brazil. Our object of study is the film Céu Aberto (1985), from the Brazilian filmmaker João Batista de Andrade; it is a documentary about the redemocratization of the country occurred in the 1980s, focused on the election process, the illness and death of Tancredo Neves, as well as the commotion and popular mobilization resulting therefrom. From this point of view, our study of the film Céu Aberto seeks to reveal the complexity of the documentary, regarding the formal aspects and content, as well as their dialogue with the broadcast journalism. The historicity of this documentary is explored not only from the questions presented in that context, but also from the personal trajectory of João Batista de Andrade. Thus, this work begins with a series of concerns of theoretical and methodological order, especially from the issue around the filmic writing of history. From the dialogue between Documentary Cinema, History of Brazil and Television, we try to explore the historical interpretation present in Céu Aberto, that is, how João Batista de Andrade discusses the complexity of military dictatorship transition to the democratic state of law.